Clinical Association of Lupus Erythematosus with Patients of Vitiligo: A Case Control Study - Azzad, Mohammad Abul Kalam; Rashid, Muhammad Munir; Noor, Syeda Fateha; Chowdhury, Abu Hena; Khondoker, Lubna (Journal of Rangpur Medical College, 2024)
Background: Vitiligo is an idiopathic acquired depigmentary skin/ mucous membrane disorder. Lupus erythematosus and vitiligo are diseases of autoimmune origin. A genetic explanation for the association between lupus erythematosus and vitiligo has recently been attempted. Objective: To find out the association of lupus Erythematosus in patients of vitiligo. Methods: This case control study was carried out in the department of Dermatology & Venereology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka during the period of January 2023 to December 2023. A total of 180 patients with and without vitiligo from both genders and different ages for case and control groups were included in the study based on inclusion and exclusion criteria. Patients were divided into two groups, 90 patients with vitiligo as cases and 90 patients without vitiligo (healthy subjects) as controls. Wood’s lamp examination was performed for diagnosis of vitiligo. LE was diagnosed based on ACR criteria and laboratory test including Complete blood count, Urinalysis, ANA, anti-ds DNA, VDRL and Skin biopsy. Patients with lupus erythematosus and patients without lupus erythematosus were considered as group I and group II respectively. Results: In this study, the mean age was found 41.7±12.8 years in case group (Vitiligo) and 42.1±13.6 years in control group (Healthy subjects).More than half (51.1%) of the patients were female in case group and 41(45.6%) in control group. There was no significant difference was found regarding age, sex, anemia, leucopenia, thrombocytopenia, proteinuria, ANA and anti ds-DNA. Family history of vitiligo was significantly higher in vitiligo patients than healthy patients (26.7% vs 12.2%). The majority 45(50.0%) presented with generalize followed by 21(23.3) acrofacial, 13(14.4%) focal, 10(11.1%) segmental and 1(1.1%) mucosal of vitiligo. Lupus erythematosus was higher in vitiligo patients than healthy patients (4.4% vs 1.1%) but the difference was not statistically significant between the two groups (p=0.184). Conclusions: This study concluded that family history of vitiligo was significantly higher in vitiligo patients than healthy patients. Lupus erythematosus was higher in vitiligo patients than healthy patients, but not statistically significant. J Rang Med Col. March 2024; Vol. 9, No. 1: 33-38